Teachers’ Evaluation and Perceptions on Adaptation of Sunrise Coursebook at Sulaymaniyah Governorate in Kurdistan Region of Iraq - Saeed, Kochar Ali (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This study aims to discover if Sunrise coursebook (levels 7, 8, and 9) could fulfill the Kurdistan’s Ministry of Educations requirements. What is teacher’s perceptions about different elements for this coursebook in these three levels. Also, This research by utilizing some specific attempts to discover possible weak points of Sunrise in the basic levels 7, 8, and 9, and whether teachers do any adaptation during their classes. If they do, what kind of adaptations do they do and how they do it? It seeks to know whether teachers do it in correct and authentic ways. For this study mixed methods are used (qualitative and quantitative), mixed method has been used for approaching the result and getting a positive outcome. The instruments used in this study are a questionnaire and a semi-structured interview. The questionnaire in this study was designed by Litz (2005). The questionnaire is categorized in a number of essential elements such as practical consideration, layout and design, activities, skills, language type, and the last one is subject and contents. For each category there are some questions. Regarding the semi-structured interview, the questions were adapted from (Nguyen, 2015). Participants of this study are teachers who have taught or are teaching (levels 7, 8, and 9) of Sunrise coursebook. The participants are from Sulaymaniyah Governorate in Kurdistan Region of Iraq (KRI). In the pilot test, 35 English teachers participated. In the real data collection 70 English teachers participated in the questionnaire while 20 English teachers participated in the interview. iv The findings of this study showed that this coursebook is suitable for these three levels and the teachers were happy with using this coursebook. Their responses to the questions indicate that appropriateness of Sunrise for these three levels is high. Also, the results show that the teachers’ perceptions about each essential element were positive. In addition, all the teachers do adaptation but in different degree; some of them just use one or two types of adaptation just because of the limited time they have in their class but some other teachers apply almost all kinds of adaptations. Finally, the results show that there is a positive relation between experience and adaptation, such that those teachers who have more experience adapt more during their classes. The present study has some practical implications. The outcomes of this study may provide useful feedback to teachers who use Sunrise and help them know more about the strengths and weaknesses of Sunrise. It may also help them to find better ways of adapting it. Meanwhile, the results may help Kurdistan’s Ministry of Education to review and improve Sunrise.

ÖZ: Bu çalışma, Sunrise adlı ders kitabının (7. 8. ve 9. sınıflara yönelik) Kürdistan Milli Eğitim Bakanlığı gereksinimlerini karşılayıp karşılamadığını bulmayı amaçlamaktadır. Bu üç seviyede bulunan ders kitabı için gerekli olan unsurlar hakkında öğretmenlerin algılarını belirlemeyi hedeflemektedir. Ayrıca bu çalışma, bazı özel girişimleri kullanarak Sunrise 7. 8. ve 9. temel düzeylerdeki olası zayıf noktaları ve ders esnasında öğretmenlerin herhangi bir uyarlama yapıp yapmadığını bulmayı amaçlamaktadır. Eğer uyarlama yapıyorlarsa, ne tür uyarlama yapmakta olduklarını ve nasıl yaptıklarını belirlemek istemektedir. Ayrıca, öğretmenlerin bunu doğru ve özgün yollarla yapıp yapmadığını bulmaya çalışmaktadır. Bu çalışmada nitel ve nicel olmak üzere karma yöntem kullanılmış olup, pozitif sonuçların elde edilmesinde karma yöntemden yararlanılmıştır. Bu çalışmada kullanılan araçlar anket ve yarı yapılandırılmış görüşmelerdir. Bu çalışmada kullanılan anket Litz (2005) tarafından tasarlanmıştır. Anket, temel unsurlara ayrılmış olup (uygulama, düzen ve tasarım, aktiviteler, beceriler, dil ve son olarak da konu ve içerik), her bir kategoriye ve yarı yapılandırılmış görüşmeye yönelik olarak sorular mevcuttur. Sorular, Nguyen (2015)’den uyarlanmıştır. Bu çalışmanın katılımcıları, Sunrise ders kitabını (7. 8. ve 9. sınıf) daha önce kullanmış veya halen kullanmakta olan öğretmenlerden oluşmaktadır. Katılımcılar, Irak Kürdistan Bölgesel Yönetimi Süleymaniye’den seçilmiştir. Pilot çalışmaya 35 İngilizce öğretmeni katılmıştır. Anket olarak yapılan gerçek çalışmaya ise 70 İngilizce öğretmeni katılmıştır. Gerçekleştirilen görüşmelere de 20 İngilizce öğretmeni katılmıştır. Bu çalışmanın bulguları, bu ders kitabının üç seviye için de uygun olduğunu ve de öğretmenlerin bu ders kitabını kullanıyor olmaktan mutluluk duyduğunu ortaya koymuştur. Sorulan sorulara verilen cevaplar, Sunrise kitabının üç seviye için de oldukça uygun olduğunu kanıtlar niteliktedir. Ayrıca sonuçlar, öğretmenlerin gerekli her unsura yönelik algılarının olumlu yönde olduğunu göstermektedir. Ek olarak, tüm öğretmenler farklı derecelerde uyarlama yaptıkları görülmüştür; bazı öğretmenler kısıtlı zamanları olduklarından sınıflarında yalnızca bir ya da iki tür uyarlama yaparken bazılarının da, neredeyse her türlü uyarlamayı yaptıkları saptanmıştır. Son olarak sonuçlar, deneyim ve uyarlama arasında pozitif bir ilişki olduğunu göstermektedir; daha çok deneyimi bulunan öğretmenler sınıf içerisinde daha çok uyarlama yapmaktadır. Bu çalışmada pratik çıkarımlar mevcuttur. Çalışmanın sonucu Sunrise kullanan öğretmenlere faydalı dönütler sağlamakla beraber öğretmenlerin, Sunrise kitabının güçlü ve zayıf yönleri hakkında daha fazla bilgi edinmelerini sağlayabilir. Ayrıca, uyarlama konusunda daha iyi çözümler bulmalarına da yardımcı olabilir. Bununla birlikte sonuçlar, Kürdistan Milli Eğitim Bakanlığı’nın Sunrise ders kitabını incelemesine ve geliştirmesine de yardımcı olabilir.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2017. Supervisor: Assist. Prof. Dr. İlkay Gilanlıoğlu.
Keywords: English Language Teaching (ELT); English Language--Study and Teaching--Suleymaniyah Governorate--Kurdish Region, Iraq; English (Second Language)--Second Language Learning--Textbookas; Coursebooks--English Language; English language Textbooks for foreign speakers